Refugeeism – Selected Socio-Political Phenomena Based on the Example of a Researched Minority Group - Bugaj, Tomasz (Porównania, 2025)
This article attempts to analyze three different socio-political phenomena pertaining to refugee categories and the religious minority group Jehovah’s Witnesses. 1. The remembrance of the deportation of believers to Siberia in 1951 for their beliefs – documented in folklore texts and autobiographies whose authors recount arrests, transport in freight cars, and harsh living conditions in Siberia. 2. The increase in the number of refugees, triggered by the Russo-Ukrainian war, which put to test the long-held beliefs and convictions. The efficient organization of refugee assistance centers, the establishment of accommodations throughout the country and the involvement of thousands of volunteers allowed for a swift distribution of aid to foreigners and contributed to their successful assimilation. 3. Removing those who break the rules from the community constitutes a form of spiritual exile, which has a long history. The author analyzes the basis of this practice, according to which the elders of the congregation ought to aid the coreligionist and, if that doesn’t produce the desired results, exile them. Spiritual exile is intended not only to protect the congregation from negative influences but also to shame, encourage reflection, and ultimately motivate return.